2000
DOI: 10.2166/wst.2000.0121
|View full text |Cite
|
Sign up to set email alerts
|

An optimised and standardised test to determine the presence of the protozoa Cryptosporidium and Giardia in water

Abstract: With funding from the European Commission, a consortium of members of the European Water Research Institutes is carrying out a programme of work with the objective of optimising and standardising a method for determining the presence in water of (oo)cysts of Cryptosporidium and Giardia. Each of the stages of the conventional analysis procedure (initial concentration, recoveryand identification and enumeration) are being investigated and the relative merits of existing and new methods are being assessed. Newly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
3
9
1
2
Order By: Relevance
“…We found in this study that when silica particles in the size range from 5 to 40 m were added to tap water to increase the turbidity to more than 10 NTU or when particles larger than 40 m were added to tap water to obtain a turbidity of 5 NTU, various amounts of particles remained on the filter after the elution process. Furthermore, a large amount of particles may also affect the IMS step, as reported by Stanfield et al (13) and Campbell and Smith (2). This was also noted from microscopic observations made in this study.…”
Section: Vol 69 2003 Particles Affect Recovery Of Cryptosporidium Omentioning
confidence: 83%
See 2 more Smart Citations
“…We found in this study that when silica particles in the size range from 5 to 40 m were added to tap water to increase the turbidity to more than 10 NTU or when particles larger than 40 m were added to tap water to obtain a turbidity of 5 NTU, various amounts of particles remained on the filter after the elution process. Furthermore, a large amount of particles may also affect the IMS step, as reported by Stanfield et al (13) and Campbell and Smith (2). This was also noted from microscopic observations made in this study.…”
Section: Vol 69 2003 Particles Affect Recovery Of Cryptosporidium Omentioning
confidence: 83%
“…As shown by the data given above, recovery of oocysts by using a Dynal anti-Cryptosporidium IMS kit yielded excellent results, and the average level of recovery was 95.1% (standard deviation, Ϯ3.4%). Using the same type of kit, Bukhari et al (1) found that the levels of oocyst recovery ranged from 68 to 83% for deionized water, while Stanfield et al (13) reported a mean level of recovery of 96.1% for treated water. The manufacturer-stated levels of recovery fell within the range from 60 to Ͼ95% for treated and raw waters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Se ha observado que la recuperación con gradientes de sacarosa es poco eficiente, variable y, en cierto grado, afecta la viabilidad de los organismos en la muestra (37). Sin embargo, un estudio más reciente realizado por Stanfield et al (38) demuestra que el Percoll-sacarosa fue el mejor gradiente de densidad para la recuperación de Giardia spp. En cuanto a los resultados para Cryptosporidium spp., se observaron pequeñas diferencias en comparación con otros gradientes de densidad pero, de igual manera, presentaron un alto porcentaje de recuperación.…”
Section: Evaluación De La Presencia Y Viabilidad De Giardia Spp Y Crunclassified
“…De otra parte, y según los estudios realizados por Stanfield et al (38), entre los filtros con mayor porcentaje de recuperación de protozoos en el análisis de aguas potables, se encuentran el Genera Filtra Max, el Cryptoscan (Aldreck) y el Envirocheck®Gelman, este último con porcentajes de recuperación para Giardia del 56,7% y para Cryptosporidium del 58,1%, evaluado a partir de muestras con concentración de 10 4 quistes u ooquistes por 10 litros.…”
Section: Evaluación De La Presencia Y Viabilidad De Giardia Spp Y Crunclassified